The Effect of Leverage and Liquidity on Dividend Policy, Profitability as Intervening Variables - Prayogo Pangestu; Bambang Mahmudi (Journal of Applied Business, Taxation and Economics Research, 2022)
The goal of this research is to see if Profitability, as measured by Return On Assets (ROA), can mediate the link between leverage and liquidity and dividend policy, as measured by the Debt To Equity Ratio (DER) and the Current Ratio (CR). The population for this study consisted of all coal mining sub-sector businesses that were registered on the Indonesia Stock Exchange between 2009 and 2018. The study employed the approach of purposive sampling. Path analysis and the Sobel test were the analytical models employed in this study. (1) Liquidity has no effect on Dividend Policy and is not significant (2) Leverage has no effect on Dividend Policy and is not significant (3) Leverage has no effect on Profitability and is not significant (4) Liquidity has no effect on Profitability and is not significant according to the findings of thisstudy. (5) Profitability has a strong and negative impact on dividend policy